CSIG-07. COMPARATIVE RNA-SEQ ANALYSIS OF GLIOMAS OF DIFFERENT MALIGNANCY IDENTIFIES FYN AS A NOVEL REGULATOR OF GBM AGGRESSIVENESS. (5th November 2018) - Comba, Andrea; Kadiyala, Padma; Dunn, Patrick; Argento, Anna; Patel, Priti; Alghamri, Mahmoud; Nunez, Felipe; G Castro, Maria; Lowenstein, Pedro
Abstract: Glioblastomas (GBM) are the most frequent and aggressive primary tumors of the brain. Fyn, a Src family kinase member, is overexpressed in human GBM. Its function, however, remains poorly understood. We analyzed the differential gene expression (DE) of highly malignant tumor (NPA: N-Ras/shp53/shATRx) compared to a less malignant one (NPAI: N-Ras/shp53/shATRx/IDH1R132H). Bioinformatics and network analysis identified Fyn as a highly connected node. This suggests that Fyn could be a regulator of GBM growth and progression. We therefore investigated the role of Fyn on glioma function in vitro and in vivo. Fyn expression levels in both human and mouse GBM cells correlated with tumor aggressiveness. Fyn knockdown in NP and NPA glioma cells decreased cell proliferation and migration. To test the activity of Fyn on tumor growth in vivo, we developed a Fyn-deficient glioma genetic model using the Sleeping Beauty transposase system. We induced Fyn knockdown in glioma tumors with different genetic drivers: NPF: N-Ras/shp53+shFyn, NPAF: N-Ras/shp53/shATRx+shFYN and NPDF: N-Ras/shp53/PDGFβ+shFYN . Fyn knockdown increased survival in all three genetically different tumors. The absence of Fyn reduced malignant neuropathological features such as pseudopalisades, ischemic necrosis, and microvascular proliferation. At the molecular level, RNA-Seq and DE analysis comparing NPF tumors with their controls, NP tumors (N-Ras/shp53) identified 573 differentially expressed genes. Bioinformatics analysis indicated altered activity in the following Gene Ontologies: "regulation of cell adhesion", "inflammatory response", and "positive regulation of cell motility". In addition, signaling pathways significantly altered in their activity included "cell adhesion molecules (CAMs)", "focal adhesion" and "ECM receptor interaction". Our results indicate that Fyn would exert its effects by regulating cell motility and interactions with the ECM. We suggest that inhibiting Fyn activity, a novel regulator of glioma malignancy, could become a relevant treatment for GBM.